Personal Dispositions Toward Criminal Recidivism in a Sample of Institutionalized Adolescents - Međedović, Janko; Kujačić, Daliborka; Knežević, Goran (Zbornik Instituta za kriminološka i sociološka istraživanja, 2012)
This study represented an attempt to identify the personality traits that predict a stable criminal behaviour in adolescence. The study included 58 subjects who were serving a correctional sentence in the Education and Correctional Home in Krusevac. Subjects were aged between 15 and 22 years, and the average age of respondents was 18.7 years (σ = 1.7). Respondents were given self-assessment questionnaires that measured: personality traits from the "Big Five" model, Disintegration, Amorality and psychopathy. Recidivism was operationalised in two ways: by the number of offences and the number of correctional treatments the individual had undergone. Predicting recidivism was done by using hierarchical regression analysis. The results show that low Agreeableness (β = -0.34, p < 0.05) from the Big Five model successfully predicted the number of criminal offences. But it lost predictive ability when psychopathy and Amorality were introduced in the model: Amorality induced by impulsivity (β = 0.65, p < 0.01) and manipulation (β = 0.60, p < 0.01) became the dominant predictors. When the number of corrective treatments that have been imposed on respondents was set as a criterion measure, the low Extraversion from the Big Five model became a significant predictor (β = -0.48, p < 0.01), and Amorality induced by brutality joined it in the next level of regression (β = 0.73, p < 0.01). The results show similarities with the findings obtained on samples of adult subjects. However, the only difference was that the behavioural psychopathy factor had no role in the prediction, which is usually the case in similar empirical studies.